Estrogens and endocrine-disrupting chemicals differentially impact the bioenergetic fluxes of mammary epithelial cells in two- and three-dimensional models - Aurélie Lacouture; Yann Breton; Cindy Weidmann; Sarah-Maude Goulet; Lucas Germain; Martin Pelletier; Étienne Audet-Walsh (Environment International, 2023)
Due to its sensitivity to hormonal signaling, the mammary gland is often referred to as a sentinel organ for the study of endocrine-disrupting chemicals (EDCs), environmental pollutants that can interfere with the estrogen signaling pathway and induce mammary developmental defects. If and how EDCs impact mammary epithelial cell metabolism has not yet been documented. Herein, to study how estrogens and EDCs modulate mammary gland metabolism, we performed bioenergetic flux analyses using mouse mammary epithelial organoids compared to cells grown in monolayer culture. Several EDCs were tested, including bisphenol A (BPA), its close derivative BPS, a new BPA replacement copolyester called TritanTM, and the herbicide glyphosate. We report that estrogens reprogrammed mammary epithelial cell metabolism differently when grown in two- and three-dimensional models. Specific EDCs were also demonstrated to alter bioenergetic fluxes, thus identifying a new potential adverse effect of these molecules. Notably, organoids were more sensitive to low EDC concentrations, highlighting them as a key model for screening the impact of various environmental pollutants. Mechanistically, transcriptomic analyses revealed that EDCs interfered with the regulation of estrogen target genes and the expression of metabolic genes in organoids. Furthermore, co-treatment with the anti-estrogen fulvestrant blocked these metabolic impacts of EDCs, suggesting that, at least partially, they act through modulation of the estrogen receptor activity. Finally, we demonstrate that mammary organoids can be used for long-term studies on EDC exposure to study alterations in organogenesis/morphogenesis and that past pregnancies can modulate the sensitivity of mammary epithelial organoids to specific EDCs. Overall, this study demonstrates that estrogens and EDCs modulate mammary epithelial cell metabolism in monolayer and organoid cultures. A better understanding of the metabolic impacts of EDCs will allow a better appreciation of their adverse effects on mammary gland development and function.